2007
DOI: 10.1091/mbc.e06-11-0987
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Chromosome Biorientation in Fission Yeast Is Enhanced by Dynein and a Minus-end–directed, Kinesin-like Protein

Abstract: Chromosome biorientation, the attachment of sister kinetochores to sister spindle poles, is vitally important for accurate chromosome segregation. We have studied this process by following the congression of pole-proximal kinetochores and their subsequent anaphase segregation in fission yeast cells that carry deletions in any or all of this organism's minus end-directed, microtubule-dependent motors: two related kinesin 14s (Pkl1p and Klp2p) and dynein. None of these deletions abolished biorientation, but fewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 49 publications
6
38
1
Order By: Relevance
“…Dynein has been also implicated in spindle formation and mitosis (Echeverri et al, 1996;Gaetz and Kapoor, 2004;Gaglio et al, 1997;Goshima and Vale, 2003;Vaisberg et al, 1993). Following NEBD, the correct positioning of dynein and its interacting proteins LIS1, NDE1 and NDEL1 on kinetochores, astral MTs and cortical sites assists in moving polarized chromosomes toward the minus ends of spindle MTs, as well as moving the spindle poles to position of the spindle within the cell (Busson et al, 1998;Coquelle et al, 2002;Cottingham and Hoyt, 1997;Faulkner et al, 2000;Gonczy et al, 1999;Grishchuk et al, 2007;O'Connell and Wang, 2000;Pfarr et al, 1990;Sharp et al, 2000a;Sharp et al, 2000b;Yan et al, 2003;Yingling et al, 2008). The role of dynein in later stages of mitosis is implied by the phenotypes induced following suppression of several subunits of dynein.…”
Section: Introductionmentioning
confidence: 99%
“…Dynein has been also implicated in spindle formation and mitosis (Echeverri et al, 1996;Gaetz and Kapoor, 2004;Gaglio et al, 1997;Goshima and Vale, 2003;Vaisberg et al, 1993). Following NEBD, the correct positioning of dynein and its interacting proteins LIS1, NDE1 and NDEL1 on kinetochores, astral MTs and cortical sites assists in moving polarized chromosomes toward the minus ends of spindle MTs, as well as moving the spindle poles to position of the spindle within the cell (Busson et al, 1998;Coquelle et al, 2002;Cottingham and Hoyt, 1997;Faulkner et al, 2000;Gonczy et al, 1999;Grishchuk et al, 2007;O'Connell and Wang, 2000;Pfarr et al, 1990;Sharp et al, 2000a;Sharp et al, 2000b;Yan et al, 2003;Yingling et al, 2008). The role of dynein in later stages of mitosis is implied by the phenotypes induced following suppression of several subunits of dynein.…”
Section: Introductionmentioning
confidence: 99%
“…In the mitotic spindle pole body, Pkl1 is required for the localization of Msd1 and the mitosis-specific spindle pole body component Wdr8; it cooperatively interacts with these two proteins to mediate the spindle anchoring, where it counteracts the outward pushing forces that are generated by Cut7 (Yukawa et al, 2015). In addition, Pkl1 also functions as the spindle assembly checkpoint, which regulates chromosome bi-orientation by mediating the spindle pole assembly (Grishchuk et al, 2007). Collectively, there are at least three roles for kinesin-14 Pkl1 in yeast.…”
Section: Tug-of-war Between Kinesin-14 and Kinesin-5 In Spindle Assemblymentioning
confidence: 99%
“…Deletion of pkl1 in fission yeast only partially interferes with chromosome congression in the spindle midzone and abrogates the mitotic checkpoint that mediates chromosome bi-orientation (Grishchuk et al, 2007). Mutation of pkl1 or simultaneous mutation of pkl1 and kinesin-5 encoding cut7 lead to three main defects in chromosome segregation (1) unequal chromosome distribution, (2) lagging chromosomes and (3) chromosome loss (Olmsted et al, 2014).…”
Section: Compartmentalized Mitotic and Meiotic Roles Of Kinesin-14mentioning
confidence: 99%
“…More recent work with cells prepared by rapid freezing and freeze-substitution fixation has confirmed that kinetochore-associated MTs end in a fibrous network (Dong et al, 2007), however, the outer plate has become less distinct as fixation methods have improved (McEwen et al, 1998). In yeast (Grishchuk et al, 2007;O'Toole et al, 1999) Table S1). By the two criteria of percent processive beads (red bars) and mean interaction time (green bars and ± s.e.m.…”
Section: Journal Of Cell Sciencementioning
confidence: 99%
“…With this exception, motor inhibition in most well-studied cells cause more problems for spindle assembly than for chromosome movement per se. When kinetochore motors are compromised at metaphase by injection of antibody (Sharp et al, 2000), mutation (Garcia et al, 2002;Mao et al, 2010;Grishchuk et al, 2007;Tanaka et al, 2007) or RNAi of components required for motor-kinetochore association (Wordeman et al, 2007;Yang et al, 2007) the results are generally changes in chromosome speed and/or an increase in the rate of chromosome loss, but the chromosomes continue to move. Thus, it is likely to be some engine other than a minus-end-directed motor that is the fundamental driver for chromosome-to-pole motion in vivo.…”
mentioning
confidence: 99%